DESIGNING INTERACTIVE DIGITAL LEARNING MODULE IN BIOLOGY - Pintalitna, Wenny; Sipahutar, Herbet; Harahap, Fauziyah (TABULARASA, 2015)
Interactive learning environment can substantially improve student learning and retention of key biology concepts. In this case report, we describe our approach for the design of interactive digital learning module to teach digestive system concepts in Grade 11 learners at SMAN 2 Balige with 180 subjects are selected according to total sampling method. The research method is the development with Dick and Carey model.Â  Subject of learning module assessment consists of two Biology matter experts, two learning module experts, one electronic media expert, three students for individual trials, ten students and teachers as small group testing, thirty students of SMAN 1 Berastagi for medium group testing, and 60 students of SMAN 2 Balige as large group testing. Quality data of product developed were collected using questionnaires. The results of developmental research showed that: (1) Module assessment by matter, learning modules and media experts were very decent criteria (88.30%, 93.98%, 88.25%); 2) Large group testing of interactive, electronic and text learning modules, respectively were 92.53%, 86.064%, 81.355% belong to very decent criteria; (3) Medium group testing respectively were 84.59%, 80.18%, 76.56% belong to decent criteria; (6) Small group testing respectively were 75.71%, 73.20%, 71.19% belong to decent criteria.